2002
DOI: 10.1101/gad.937102
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling plays an essential role in neuronal specification of the dorsal spinal cord

Abstract: In the developing spinal cord, signals from the roof plate are required for the development of three classes of dorsal interneuron: D1, D2, and D3, listed from dorsal to ventral. Here, we demonstrate that absence of Wnt1 and Wnt3a, normally expressed in the roof plate, leads to diminished development of D1 and D2 neurons and a compensatory increase in D3 neuron populations. This occurs without significantly altered expression of BMP and related genes in the roof plate. Moreover, Wnt3a protein induces expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
214
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(223 citation statements)
references
References 36 publications
(58 reference statements)
8
214
0
Order By: Relevance
“…These data suggest that the Shh and BMP signalling pathways intersect and that BMPs act to limit the ventralizing activity of Shh. In addition to BMPs, Wnt proteins emanating from the dorsal midline have also been found to affect neural progenitor behaviour and neuronal identity (Muroyama et al 2002). Wnt signals appear to promote progenitor proliferation throughout the neural tube (Megason & McMahon 2002;Chesnutt et al 2004), and have also been suggested to inhibit Shh signalling and, consequently, the generation of ventral cell types (Robertson et al 2004).…”
Section: Gli Proteins Mediate Graded Shh Signallingmentioning
confidence: 99%
“…These data suggest that the Shh and BMP signalling pathways intersect and that BMPs act to limit the ventralizing activity of Shh. In addition to BMPs, Wnt proteins emanating from the dorsal midline have also been found to affect neural progenitor behaviour and neuronal identity (Muroyama et al 2002). Wnt signals appear to promote progenitor proliferation throughout the neural tube (Megason & McMahon 2002;Chesnutt et al 2004), and have also been suggested to inhibit Shh signalling and, consequently, the generation of ventral cell types (Robertson et al 2004).…”
Section: Gli Proteins Mediate Graded Shh Signallingmentioning
confidence: 99%
“…The expression of olig3 in the lateral domain of the neuroectoderm at the shield stage suggests that early genetic events restrict its expression ventrally. Because Wnt signaling is required for polarization of the early vertebrate embryo and the specification of the dorsal neuroectoderm (29,30), olig3 might be implicated in the regulation of neural plate and neural crest fates under the control of the blastula Wnt gradient. To test this hypothesis, we analyzed the olig3 expression pattern in embryos in which the Wnt signaling is increased or impaired.…”
Section: D)mentioning
confidence: 99%
“…Ventrally, Sonic hedgehog (SHH) drives the position and identity of ventral neurons (Briscoe and Novitch, 2008). In addition to BMPs, Wnt proteins also regulate dorsal progenitor proliferation and identity (Muroyama et al, 2002). Recently, evidence have been obtained showing that SHH also influences NE cell proliferation and survival (Cayuso et al, 2006), suggesting that gradients emanating from opposite poles in the neural tube, BMPs/Wnts dorsally and SHH ventrally, simultaneously control neural growth and patterning.…”
Section: Introductionmentioning
confidence: 99%